Evaluation of an international classification of functioning, disability and health-based rehabilitation for thermal burn injuries: a prospective non-randomized design - Neubauer, Hubert; Stolle, Annette M.; Ripper, Sabine; Klimitz, Felix; Ziegenthaler, Hans; Strupat, Mareike Lea; Kneser, Ulrich; Harhaus-Wähner, Leila (Trials, 2019)
Severe burn injuries result in relevant restrictions of physical capacity as well as psychological and social integrity and require a specialized rehabilitation. There is a common agreement, among national as well as international burn associations, that burn rehabilitation is a complex, dynamic process which needs an interdisciplinary and specialized treatment team. There is wide agreement that more research is needed in this field.
Gesehen am 27.01.2020